2015
DOI: 10.3741/jkwra.2015.48.3.169
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on Fluvial Geomorphological Characteristics based on Past and Present Data for River Restoration: An Application to the Miho River and the Naesung River

Abstract: As a basic work for river restoration, analysis on fluvial geomorphological characteristics is made using past and present data to understand close-to-nature geomorphic status. The Miho and the Naesung Rivers are targets of this study. Fluvial geomorphic variables including valley-floor width, sinuosity, bankfull width, channel gradient, bed material size, bankfull discharge and unit stream power are evaluated with dominant processes. Though common sand-bed rivers with similar catchment area, the Miho and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 16 publications
0
8
0
1
Order By: Relevance
“…The coefficient of determination (R 2 ), root mean square error (RMSE), and Nash Sutcliffe Efficiency (NSE) have been adopted in this study as the indicators to verify the accuracy of the predicted results. As mentioned previously, each performance metric is described in Equations ( 8), ( 9), (10), and (11), respectively.…”
Section: Performance Metrics Of Predictionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The coefficient of determination (R 2 ), root mean square error (RMSE), and Nash Sutcliffe Efficiency (NSE) have been adopted in this study as the indicators to verify the accuracy of the predicted results. As mentioned previously, each performance metric is described in Equations ( 8), ( 9), (10), and (11), respectively.…”
Section: Performance Metrics Of Predictionsmentioning
confidence: 99%
“…Kim et al [10] developed an LSTM model to predict the water level using the historical water level and rainfall data at the same point, and the applicability of the model was proven by evaluating the prediction accuracy of the model according to the lead time. Lee et al [11] simulated the outflow at the lower Mekong River using both physical models and data-driven models, and the performance levels of these two models were evaluated. The authors concluded that the accuracy of the data-driven model was better, demonstrating that the data-driven model in fact outperformed the conventional physical model.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, due to the local economic structures being dependent on primary industries (e.g., agriculture, fishing, and forestry), although the sensitivity to climate change and exposure to extreme weather events are high, the budgets and response policies for preventing natural disasters are highly limited. Therefore, predicting future water resource variability due to long-term and short-term variations in precipitation and establishing response policies is a key issue in terms of reducing socio-economic damage and securing the safety of people [2]. In order to solve this problem and promote efficient basin development, a rainfall-runoff analysis must be carried out incorporating the effects of climate change.…”
Section: Andmentioning
confidence: 99%
“…The Mekong River is an international river shared by six countries: China, Myanmar, Laos, Thailand, Cambodia, and Vietnam. It has a length of 4800 km, a total basin area of 795,000 km 2…”
Section: Introductionmentioning
confidence: 99%
“…1). 내성천은 우리나라의 대표적인 모래 하 상 하천으로서 보전가치가 높지만 현재 내성천의 중류 에 영주댐이 건설되어 앞으로 급격한 환경 변화가 예상 되는 하천이다 (Lee et al 2015).…”
Section: 서 론unclassified